2015
DOI: 10.1007/s10719-015-9641-3
|View full text |Cite
|
Sign up to set email alerts
|

N-glycoprotein macroheterogeneity: biological implications and proteomic characterization

Abstract: Glycosylation is a co- and post-translational modification that is critical for the regulation of the biophysical properties and biological activities of diverse proteins. Biosynthetic pathways for protein glycosylation are inherently inefficient, resulting in high structural diversity in mature glycoproteins. Macroheterogeneity is the structural diversity due to the presence or absence of glycans at specific glycosylation sites, and is caused by inefficiency in the initial transfer of glycans to proteins. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 182 publications
1
79
0
Order By: Relevance
“…The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36). Few studies have shown the relation between protein primary sequence and the observed glycan profile.…”
mentioning
confidence: 99%
“…The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36). Few studies have shown the relation between protein primary sequence and the observed glycan profile.…”
mentioning
confidence: 99%
“…The use of such nonconsensus sequons seems to be more frequent in rodents, where even glutamine-linked glycosylation has been reported (14). Low efficiency N-glycosylation in these noncanonical sequons is consistent with a role of the canonical sequon in recognition and high-affinity binding to OST to promote glycan transfer (15). Mammalian N-glycans share a common trimannosylchitobiose core comprised of three mannose (Man) and two N-acetylglucosamine (GlcNAc) residues, extended with a variety of monosaccharides including Man, GlcNAc, galactose (Gal), fucose (Fuc), N-acetylgalactosamine (GalNAc) and sialic acids such as N-acetylneuraminic acid (NeuAc) and N-glycolylneuraminic acid (NeuGc).…”
mentioning
confidence: 54%
“…Glycoforms of a single protein can differ in the glycan structures attached at a specific site (defined as microheterogeneity) or in the proportion of sites that are occupied (defined as macroheterogeneity) (13). The complex nature of protein glycosylation and subsequent structural diversity of glycoproteins present significant challenges when defining the glycosylation profile of glycoproteins.…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…This may be due to the small size of the theoretical peptide 446 KNISIQD 452 . There are conflicting reports on occupancy at N447 using site-directed mutagenesis combined with gel-electrophoresis (13,14). However, the crystal structure of NDV V4-VAR F revealed up to three residues (GlcNAc 2 Man 1 ) at N447 in trimers of F, indicting this site can be occupied.…”
Section: Supplemental Collisional Activation Of Non-dissociated Peptimentioning
confidence: 99%
See 1 more Smart Citation